Synthesis, characterization, and biological evaluation of new oxime-phosphazenes - Koran, Kenan; Ozkaya, Ahmet; Ozen, Furkan; Cil, Erol; Arslan, Mustafa (SPRINGER, 2013)
Hexachlorocylotriphosphazene (1) was reacted with 4-hydroxy-3-methoxybenzaldehyde to give hexakis[(4-formyl-2-methoxy)phenoxy]cyclotriphosphazene (2). Hexakis[(4-(hydroxyimino)2-methoxy)phenoxy]cyclotriphosphazene (3) was synthesized by reaction of 2 with hydroxlamine hydrochloride in pyridine. Compound 3 was reacted with benzyl chloride, acetyl chloride, allyl bromide, benzoyl chloride, propanoyl chloride, 4-methoxybenzoyl chloride, 2-chlorobenzoyl chloride, chloroacetyl chloride, methyl iodide, and thiophene-2-carbonyl chloride. From these reactions, full or partially substituted compounds were obtained, usually in high yields. Pure or defined products could not be obtained from reaction of 3 with methacryloyl chloride and O-acetylsalicyloyl chloride. The structures of the compounds were determined by elemental analysis, and IR, H-1, C-13, and P-31 NMR spectroscopy. The synthesized compounds were screened for in-vitro antimicrobial activity against two Gram-positive bacteria (Staphylococcus aureus and Enterococcus faecalis), two gram-negative bacteria (Escherichia coli and Klebsiella pneumonia), and fungal strains (Aspergillus niger, and Candida albicans) by the agar well diffusion method. Few compounds had significant activity against both Gram-positive and Gram-negative bacteria. None of the compounds had antifungal activity except compounds 7 and 9, which had moderate activity.
Keywords: Hexachlorocyclotriphosphazene; Phosphazene; Oxime-phosphazenes; Antibacterial; Antifungal; DICHLOROPHOSPHORYL-P-TRICHLOROPHOSPHAZENE; CYCLOTRIPHOSPHAZENE DERIVATIVES; LINEAR PHOSPHAZENES; CRYSTAL-STRUCTURE; YEAST-CELLS; SCHIFF-BASE; COMPLEXES; BACTERIAL; ALKYL; CYCLOPHOSPHAZENES; Chemistry